A preliminary analysis on the performance of business and economics students in relation to the university selection method / Syed Azizi Wafa, Rosie Mohidin and Caroline Geetha - Wafa, Syed Azizi; Mohidin, Rosie; Geetha, Caroline (2004)
In line with the education ministries effort to create a world class education system, the selection method used to select students to enter the public universities were converted from the quota system to the meritocracy system in 2002. The meritocracy system will enable students with better academic merits to be selected to pursue their education in the public universities irrelevant to their ethnicity. This will enhance the quality of students entering the public universities and fulfill the goal of the nation to create a knowledge society. The meritocracy system of selection currently used have received criticism from academicians, practitioners and the politicians since the new system did not take into consideration the social, cultural and economic background of the students. Thus a study was conducted to identify whether the students whom we have selected according to the meritocracy system are able to perform well in universities in comparison with the students selected using the quota system. This is done by comparing the educational performance of the students using the quota system with the educational performance of the students selected using the meritocracy system m the field of business and economics. The study reveled that overall the mean cumulative grade point average of students had significantly decreased from the quota system to the merit system. In addition, there is also an indication of a fall in the classification where the majority of the students classified under the cumulative grade point average of 3.00 and above in the quota system had fallen to a cumulative grade point average of 2.00 to 3.00 in the merit system